1986
DOI: 10.1007/bf00219324
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of S-100 protein and parvalbumin on protein kinases and phosphoprotein phosphatases from brain and skeletal muscle

Abstract: In the eluted fractions of histone-treated crude extracts separated by Sephadex G-200 filtration, multiple protein kinase (PK) activities, including three from brain and two from skeletal muscle, were augmented by both S-100 protein and parvalbumin on the phosphorylation of endogenous substrates. One additional PK activity suppressed by both S-100 and parvalbumin was also found in muscle. In comparison, phosphoprotein phosphatases (PPase), which were also prepared by the same procedure of initial step of histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, perineuronal nets avoid calretinin-positive neurons (Liith et al, 1992). Notwithstanding considerable effort, an effect of parvalbumin or calbindin D-28k (Blum et al, 1973;Kuo et al, 1986) on the activity of kinases or phosphatases has never been convincingly demonstrated. Further studies with modern, more refined techniques are warranted.…”
Section: Ca2 Pyramidalmentioning
confidence: 99%
“…However, perineuronal nets avoid calretinin-positive neurons (Liith et al, 1992). Notwithstanding considerable effort, an effect of parvalbumin or calbindin D-28k (Blum et al, 1973;Kuo et al, 1986) on the activity of kinases or phosphatases has never been convincingly demonstrated. Further studies with modern, more refined techniques are warranted.…”
Section: Ca2 Pyramidalmentioning
confidence: 99%
“…S-100 had many functions in cell-cell adhesion protein synthesis and energy metabolism excitation contraction and structure of biochemistry of the thick and thin filaments in skeletal muscle. S-100 protein has been reported to regulate protein kinase activity (Kuo et al, 1986a). Also, S -100 protein had detected in peripheral nerve cells.…”
Section: Meanwhile These Were In One Line With Fredrich Et Al (2007)mentioning
confidence: 99%
“…These proteins play a versatile regulatory role in mammalian cells [1, [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%